2021
DOI: 10.1007/s12032-021-01484-z
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin inhibition induces autophagy, apoptosis, G0/G1 cell cycle arrest in agonist-activated V2R receptor in breast cancer cells

Abstract: Non-visual arrestins (β-arrestins) are endocytic proteins that mediate agonist activated GPCRs internalization and signaling pathways in an independent manner. The involvement of β-arrestins in cancer invasion and metastasis is increasingly reported. So, it is hypothesized that inhibition of β-arrstins may diminish the survival chances of cancer cells. This study aimed to evaluate the in vitro impact of inhibiting β-arrestins on the autophagic and/or apoptotic responsiveness of breast cancer cells.We used Barb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…However, the crosstalk between inhibitors of these proteins and non-endocytic targets is not well explored. Previously, we demonstrated that the inhibition of the interaction between β-arrestin, an endocytic accessory protein, and AP2 adaptor protein, decreased the viability of TNBC cells [22]. In the present study, Dyn2, (integral endocytic proteins with an intrinsic GTPase activity) was inhibited by 3-hydroxynaphthalene-2-carboxylic acid-(3,4-dihydroxybenzylidene)-hydrazide (commonly known as Dynasore) to explore the associated side effects on TNBC cells viability and their metastasis, especially when cells were prestimulated with exogenous AVP hormone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the crosstalk between inhibitors of these proteins and non-endocytic targets is not well explored. Previously, we demonstrated that the inhibition of the interaction between β-arrestin, an endocytic accessory protein, and AP2 adaptor protein, decreased the viability of TNBC cells [22]. In the present study, Dyn2, (integral endocytic proteins with an intrinsic GTPase activity) was inhibited by 3-hydroxynaphthalene-2-carboxylic acid-(3,4-dihydroxybenzylidene)-hydrazide (commonly known as Dynasore) to explore the associated side effects on TNBC cells viability and their metastasis, especially when cells were prestimulated with exogenous AVP hormone.…”
Section: Discussionmentioning
confidence: 98%
“…Also, other studies have reported that it suppressed cell proliferation, migration and enhanced the antitumor e cacy of cisplatin in osteosarcoma via STAT3 pathway [20], reduced the metastasis of cervical cancer [12] (Lee et al, 2016) and induced apoptosis in NSCLC cells [21]. Recently, we reported that the inhibition of early endocytic events of CME, through inhibiting the interaction between β-arrestin and AP2 adaptor protein induced both apoptosis and autophagy in invasive breast cancer [22].…”
Section: Introductionmentioning
confidence: 91%
“…78 Starvation-induced apoptosis and autophagy also trigger cell cycle arrest in different cancer cell types. 81,82 Recent research has also suggested that plasma exposure inhibits cell cycle progression and promotes apoptosis or autophagy in cancer cells in many types of cancer cells. [83][84][85] Combining CAP with starvation may amplify cell cycle arrest, cell death and therapeutic outcomes in animal models, but more research is needed to pinpoint the exact modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…The complex of Atg5 and Bcl‐X then contributes to apoptosis induction 78 . Starvation‐induced apoptosis and autophagy also trigger cell cycle arrest in different cancer cell types 81,82 . Recent research has also suggested that plasma exposure inhibits cell cycle progression and promotes apoptosis or autophagy in cancer cells in many types of cancer cells 83–85 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteins have been shown to be scaffolded by β‐arrestin isoforms 1 and 2 (β‐arr1 and β‐arr2) within the cytoplasm and migrate to the nucleus in regulating several cellular processes (Peterson & Luttrell, 2017). β‐Arrs regulate several cellular functionalities such as cell proliferation, cell cycle regulation, inhibition of cell apoptosis, angiogenesis, and others (Donia et al, 2021). These functions are common attributes of a cancer phenotype.…”
Section: Introductionmentioning
confidence: 99%